Health Promotion in Health Care – Vital Theories and Research 2021
DOI: 10.1007/978-3-030-63135-2_2
|View full text |Cite
|
Sign up to set email alerts
|

The Overarching Concept of Salutogenesis in the Context of Health Care

Abstract: Two concepts that widely impact on our ways to work with health is health promotion and salutogenesis (For a quick overview of the concept of salutogenesis, read Lindström B. & Eriksson M. (2010). The Hitchhiker’s Guide to Salutogenesis. Folkhälsan Research Center). The concept of health promotion was voted for use by the participants of World Health Organization (WHO) general assembly in 1978. And after 8 years, the concept of health promotion was filled with content by the WHO meeting in Ottawa in 1986. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…If we return to the core policy document of health promotion, the Ottawa Charter [7], one of the strategies for health development was reorienting health services. This approach appears to have received little attention, and its development has been particularly slow [65][66][67]. With a salutogenic perspective on health care, the focus on both patients and professionals can be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…If we return to the core policy document of health promotion, the Ottawa Charter [7], one of the strategies for health development was reorienting health services. This approach appears to have received little attention, and its development has been particularly slow [65][66][67]. With a salutogenic perspective on health care, the focus on both patients and professionals can be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, workplace well-being has become a measure of the absence of mental health disorders. A salutogenic approach 24 25 that measures positive determinants, context, mechanisms, and individual and group well-being should be preferred when considering doctor well-being. 26…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The thoughts of Aaron Antonovsky (1979) followed a similar path, when in the 1970s he studied the adaptation to the climacteric among women of Jewish origin who survived the atrocities of extermination camps during World War II. The sociologist discovered with amazement that less than twenty years after the trauma of the Holocaust, as many as 29% of the women surveyed led a satisfying life, maintaining a relatively high level of somatic and mental health (Cierpiałkowska, Sęk, 2019;Espnes, Moksnes, Haugan, 2021). Analysing the results of these studies, Antonovsky showed a certain perversity, thus setting out a new paradigm in thinking about health -the salutogenetic orientation.…”
Section: Noo-psychotheory and The Meaning Of Lifementioning
confidence: 99%